ANALYSIS OF THE RELATIONSHIP OF THE COVID-19 PANDEMI WITH THE STATE OF THE INDONESIAN COMMUNITY ECONOMY FOR THE 2019-2020 PERIOD - Ikanti Sri Nafiah (Universitas Islam Indonesia, 2021)
The Covid-19 pandemic has been around for a long time in Indonesia. This pandemic has had a major impact, one of which is on the economic level of the Indonesian people which resulted in a decrease in the economic level to poverty in Indonesian society. This study aims to analyze the relationship between the covid-19 pandemic and the economic level of Indonesian society by using a literature study with data collection techniques using data reduction, where the author collects and analyzes existing data, then concludes it so that it becomes a conclusion that is relevant to this research. From the results of data collection from several sources conducted by the author, the covid19 pandemic has made the Indonesian economy experience a decline, the impact is increased poverty, before the pandemic the number of poor people nationally for the period March 2018 to September 2019 decreased from 25,95 million to 24,79 million, but after the pandemic the number of poor people soared, in March 2020 there was a spike in the national poor to 26,42 million soul. The author concludes that the link between the COVID-19 pandemic and the economic level of the Indonesian people is making poverty in Indonesia worse. Keywords: covid-19 pandemic, economic level, poverty.